Effect of Pan Feeder System and Chain Feeder System Affecting the Uniformity of the Chicken Flock - Taemchuay, Duangkamol; Khiewnakhoo, Nusaba; Boonmee, Wimonmat; Bunya-atichart, Kanokpon; Punmalai, Suteerawat; Yenphayab, Charatchai (Journal of Mahanakorn Veterinary Medicine, 2023)
The purpose of this study was to study the system of feeding chickens between the pan feeder system and the chain feeder system that affects flock uniformity. The experiment was carried out in broilers. 18,552 Arbor Acres Plus S, 4-8 weeks old. Free-release culture is carried out in an evaporative cooling system (EVAP) house that controls temperature, humidity, light, and ventilation within the house. The experimental groups were grouped into 2 groups as follows: Group 1 was house 1 (A1), housed 9,180 chickens, pan feeder system, and group 2 was house 6 (B6), housed. 9,372 chickens, chain feeder system. The trial period was 4 weeks, and evaluating production efficiency such as body weight, herd uniformity coefficient of variance. The results showed that the pan feeder system and the chain feeder system had no effect on flock uniformity (p>0.05).